Encouragement and distortionary effects of conditional cash transfers - Gharad Bryan; Shyamal K. Chowdhury; Ahmed Mushfiq Mobarak; Melanie Morten; Joeri Smits (Yale University, Economic Growth Center, 2021)
Conditional cash transfer (CCT) programs have become increasingly popular as a development strategy. These programs aim to reduce poverty or achieve other social goals by making the transfers conditional upon the receivers' actions. Conditions are designed to encourage some desirable behavior that recipients might otherwise under-invest in. An unintended consequence of the conditionality may be to distort recipients' actions in ways that lower their welfare. The transfer size plays an important role in shaping such distortionary effects. In certain circumstances, a larger transfer increases distortion more than that it raises benefits from stronger encouragement, implying that (i) there is an optimal transfer size for CCTs, and (ii) unconditional cash transfers (UCTs) may be better than CCTs when the transfer amount is large. We illustrate a range of distortions arising from CCT programs around the world. We then introduce an experimental design that permits a test of this distortionary effect, and implement it in a cash transfer program conditional on seasonal labor migration in rural Indonesia. We find that when the transfer size exceeds the amount required for travel expenses, the distortion created induces additional individuals to migrate who have lower (possibly even negative) migration returns, weakening overall program impacts.
Keywords: I38; O15; J48; 330; Conditional cash transfers; Distortion; Seasonal migration